Application of simulation teaching in transthoracic echocardiographic training - GUO Xiao-xiao, GUO Li-lin, WEI Tong-hui, FANG Li-gang (Jichu yixue yu linchuang, 2022)
Objective To compare the effect of simulation training and tradition training methods in the teaching of acquisition skills of transthoracic echocardiography (TTE). Methods From July 1, 2020 to April 30, 2021, 30 doctors receiving TTE training in the department of cardiology of Peking Union Medical College Hospital were recruited and randomly divided into two groups: the tradition training group and the simulation group. After training, the view-specific transthoracic echocardiographic examination scores and the total operation time were compared between the two groups. Results The duration of the examinations on TTE acquisition in the simulation group was significantly shorter than that in the tradition training group [(471±66)s vs (530±60)s](P＜0.05). The total score of the view-specific transthoracic echocardiographic examination in the simulation group was significantly higher than that in the tradition training group (42.7±2.5 vs 38.7±3.0, P＜0.01), especially in the parasternal aortic short axis view (3.9±0.9 vs 3.2±0.4, P＜0.05), apical two chamber view (4.0±0.8 vs 3.2±0.9, P＜0.05) and superior sternal fossa view (3.8±0.8 vs 2.6±1.1, P＜0.01). The satisfaction of the simulation group was significantly higher than that of the tradition training group (P＜0.05). Conclusions The application of simulation teaching in TTE training is feasible and useful with acquired better skills in TTE image acquisition and improved student satisfaction.